PUSAT BUDAYA PALEMBANG DI 13 ILIR, SUMATERA SELATAN - Febian Pratama (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
In terms of beyond ecology, by looking at the culture ecology side. Indonesia is an archipelagic country that has the wealth and diversity of the archipelago’s culture which is an attraction in itself in the eyes of the world. However, the current cultural conditions are starting to be abandoned by some Indonesian people, which may not be separated from the times and technology as well as the entry of foreign cultural influences. For example the Palembang city, which is the capital city of South Sumatra as the center of government, recreation, cultural, and trade center. Culture in the region becomes an important role in it that should not be lost. So the site is located in Palembang close to the Musi River. The younger generation must play an important role in preserving the diversity of culture and local architecture that Indonesia has. Palembang itself does not yet have a place to accommodate the existing culture. So the project is designed based on cultural functions by creating a cultural center that is believed to be very important for the community and the nation’s successors in order to keep a culture that exists in Palembang based on beyond ecology. Keywords: Cultural; Culture; Palembang; Younger generation AbstrakDalam persoalan ekologi melampaui, dengan melihat pada sisi ekologi budaya. Indonesia merupakan negara kepulauan yang memiliki kekayaan dan keragaman budaya nusantara yang menjadikannya sebuah daya tarik sendiri di mata dunia. Namun kondisi kebudayaan yang ada saat ini mulai ditinggalkan oleh sebagian masyarakat Indonesia yang mungkin tidak terlepas dari perkembangan zaman dan teknologi serta masuknya pengaruh budaya luar. Misalnya kota Palembang, dimana sebagai ibukota Provinsi Sumatera Selatan yang merupakan pusat pemerintahan, pusat rekreasi, pusat permukiman, pusat perdagangan dan pusat kebudayaan. Kebudayaan di wilayah tersebut menjadi peran penting didalamnya yang seharusnya tidak hilang. Sehingga pemilihan tapak berlokasi di Palembang  yang berdekatan dengan Sungai Musi. Generasi muda seharusnya menjadi peran penting dalam menjaga kelestarian keanekaragaman budaya dan arsitektur lokal yang dimiliki Indonesia. Mengingat bahwa di Palembang itu sendiri belum memiliki sebuah wadah untuk menampung kebudayaan yang ada. Sehingga proyek ini dirancang berbasis pada fungsi kultural dengan membuat sebuah pusat budaya yang diyakinkan menjadi sangat penting bagi masyarakat maupun penerus bangsa agar tetap dapat melestarikan sebuah kultural yang ada di Palembang dalam konteks ekologi melampaui.